2012
DOI: 10.2172/1057838
|View full text |Cite
|
Sign up to set email alerts
|

Trial Application of the Facility Safeguardability Assessment Process to the NuScale SMR Design

Abstract: Executive SummaryThe International Atomic Energy Agency (IAEA) is tasked with verifying that commitments made by States as part of their safeguards agreements with the IAEA are fulfilled. The IAEA verifies declarations made by States and detects undeclared activities in States through the implementation of a Safeguards Approach (SA) for the facility and a State Level Approach (SLA) for the entire state. At the facility level, the SA consists of measures to verify the special fissionable material present and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Safeguards implementation at the Rokkasho reprocessing plant in Japan showed that SBD initiation and dialogue with the IAEA early in the design process is critical [4]. Additionally, with trends towards standardized, and in some cases regulator-certified, NPP designs, rather than individual designs for specific locations, a safeguards-by-design approach would be of further value, particularly for Small Modular Reactors (SMRs) [5] [6], to ensure that the design can readily accommodates the safeguards measures the IAEA might apply…”
Section: Purposementioning
confidence: 99%
See 2 more Smart Citations
“…Safeguards implementation at the Rokkasho reprocessing plant in Japan showed that SBD initiation and dialogue with the IAEA early in the design process is critical [4]. Additionally, with trends towards standardized, and in some cases regulator-certified, NPP designs, rather than individual designs for specific locations, a safeguards-by-design approach would be of further value, particularly for Small Modular Reactors (SMRs) [5] [6], to ensure that the design can readily accommodates the safeguards measures the IAEA might apply…”
Section: Purposementioning
confidence: 99%
“…Because most fast reactors are in the earlier stages of development and design maturity, designers have a greater opportunity for inclusion of safeguards in the design considerations. These considerations include:  early provision of design information before it is finalized [5][6][7][8]  provision of additional information by the State regarding nuclear facilities and activities related to the fuel cycle  hardened, secure storage for plutonium, HEU or transuranic fuel  advanced, redundant containment and surveillance systems  continuous, unattended NDA to monitor fuel movements that can distinguish between fissile and fertile or non-nuclear material item  the implications of minor-actinide bearing fuels on the implementation of safeguards [27]  clear segregation of any hot cells and pin handling equipment from the rest of the reactor facility to allow them to be placed under more stringent safeguards measures without affecting the majority of the facility's item accounting status …”
Section: Fast Reactorsmentioning
confidence: 99%
See 1 more Smart Citation